Oxytocin is implicated in social memory deficits induced by early sensory deprivation in mice. Issue 1 (December 2016) - Zhang, Jin-Bao; Chen, Ling; Lv, Zhu-Man; Niu, Xue-Yuan; Shao, Can-Can; Zhang, Chan; Pruski, Michal; Huang, Ying; Qi, Cong-Cong; Song, Ning-Ning; Lang, Bing; Ding, Yu-Qiang
Abstract Early-life sensory input plays a crucial role in brain development. Although deprivation of orofacial sensory input at perinatal stages disrupts the establishment of the barrel cortex and relevant callosal connections, its long-term effect on adult behavior remains elusive. In this study, we investigated the behavioral phenotypes in adult mice with unilateral transection of the infraorbital nerve (ION) at postnatal day 3 (P3). Although ION-transected mice had normal locomotor activity, motor coordination, olfaction, anxiety-like behaviors, novel object memory, preference for social novelty and sociability, they presented deficits in social memory and spatial memory compared with control mice. In addition, the social memory deficit was associated with reduced oxytocin (OXT) levels in the hypothalamus and could be partially restored by intranasal administration of OXT. Thus, early sensory deprivation does result in behavioral alterations in mice, some of which may be associated with the disruption of oxytocin signaling.